Toxicity of Sanguinaria canadensis L. as Compared to Aloe vera L. against Brine Shrimp (Artemia salina) Using the Probit Methodology - Mahwish Ahmed Karim; Ghazala H. Rizwani; Afaq Ahmed Sidddiqui; Muhammad Farhanullah Khan; Mansoor Ahmed (Journal of Pharmacy and Nutrition Sciences, 2015)
Toxicity study of Sanguinaria canadensis L. was determined as compared to Aloe vera (L.) Burm. f. against brine shrimp (Artemia salina). Upon statistical analysis of obtained toxicity bioassay data through the method of probits, LC50 of Sanguinaria canadensis was estimated as 0.021 mg/ml, with (95% C.I : 0.0091-0.0485) whereas Aloe vera was found to be almost non-toxic showing relatively higher LC50 that is, 180783.7 mg/ml. These results show that Aloe vera that is being used widely as an herbal medicine throughout the world, could be used safely for other various expected purposes for instance IPM etc. where the excessive amount is anticipated to drain into the sea ecosystem ultimately.